Complication Rates of Medical Thoracoscopy under Local Anesthesia: A Multicenter Study - Iqbal, Qaisar; Rehman Khan, Sarmad Abdul; Imran Sharif, Muhammad; Waseem Yaseen, Hafiz Muhammad; Fayyaz Malik, Maryyam; Kumar, Pavan; Haseeb, Abdul; Tahir, Imran (Journal of Neonatal Surgery, 2025)
Background: To determine the complication rates and diagnostic yield of medical thoracoscopy under local anesthesia across multiple tertiary care centers. Methods:This prospective observational study included 71 adult patients undergoing diagnostic medical thoracoscopy at three tertiary care hospitals over 12 months. Baseline demographics, procedural details, intraoperative findings, complications, and hospital course were recorded using standardized forms. Complications were categorized as immediate or early (within 72 hours). Statistical analysis included Chi-square and t-tests, with a p-value <0.05 considered significant. Results:The mean age was 54.2 ± 12.7 years, with 59.2% male patients. Suspected malignant pleural effusion was the most common indication (53.5%). Pneumothorax (12.7%), fever (9.9%), and minor bleeding (8.5%) were the most frequent complications. Serious adverse events were rare, with empyema occurring in 2.8% and re-expansion pulmonary edema in 1.4% of cases. No procedure-related mortality was observed. The overall diagnostic yield was 88.7%, with malignancy confirmed in 49.3% and tuberculosis in 25.4% of patients. Conclusion:Medical thoracoscopy under local anesthesia demonstrates a low complication rate and high diagnostic yield across diverse tertiary care settings. Adherence to standardized protocols and widespread use of ultrasound guidance appear to contribute to procedural safety..